2021
DOI: 10.2166/nh.2021.168
|View full text |Cite
|
Sign up to set email alerts
|

Dew formation characteristics of meadow plants canopy at different heights in Hulunbuir grassland, China

Abstract: A plant's foliar uptake of dew can mitigate the adverse effects caused by drought stress. However, in grassland ecosystems, it is inconclusive whether the dew condensation characteristics of plants at different heights are consistent. In this study, we wanted to know whether plant height had a significant effect on the formation of dew. In addition, we wanted to understand the difference of dew formation between C3 plant Leymus chinensis (LC) and C4 plant Cleistogenes squarrosa (CS) which have different height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…This phenomenon occurs where dews or precipitation settles on the leaf's surfaces of plants, absorb and which encourages the survival of plant species which might lead to fruit/or seed formation before the plant dry out to face severe drought. This corroborates Ye and Peng (2011) and Xie et al (2021) in their findings that dew serves as sources of water for plant species survival in some places of low seasonal rainfall especially in arid and semi-arid environment.…”
Section: Correlation Analysis Of Weed Species Abundance and Soil Phys...supporting
confidence: 89%
“…This phenomenon occurs where dews or precipitation settles on the leaf's surfaces of plants, absorb and which encourages the survival of plant species which might lead to fruit/or seed formation before the plant dry out to face severe drought. This corroborates Ye and Peng (2011) and Xie et al (2021) in their findings that dew serves as sources of water for plant species survival in some places of low seasonal rainfall especially in arid and semi-arid environment.…”
Section: Correlation Analysis Of Weed Species Abundance and Soil Phys...supporting
confidence: 89%
“…Short grass becomes wet due to the partial condensation of water vapor evaporating from the soil during cool calm nights (Monteith, 1957). Xie et al (2021) found that as plant height increased, dew formation also increased, but was limited within a species in grassland. Between species, the grass with slender leaf structure accumulated similar dew at lower leaf heights compared to broader leaf species, indicating that surface area is very important in dew formation.…”
Section: Introductionmentioning
confidence: 99%